TEACHER'S NON-LANGUAGE COMMUNICATIVE COMPETENCE OF FOREIGN LANGUAGES IN THE CONTEXT OF THE EUROPEAN INTEGRATION PROCESS UKRAINE - I.O. Tyalleva (Academy of Cognitive and Natural Sciences, 2008)
In the paper foreign language communicative competence of the teachers of foreign languages is discussed as a factor of success of Ukrainian integration into European educational sphere. The conditions of improvement of foreign language communicative competence developing process is presented in the system of in-service education.